Konsep Ganbaru dalam Lirik Lagu GUTS! oleh Arashi - Ahyu Wibowo; Frida Philiyanti; Yuniarsih (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2025)
This study aims to explore the concept of "ganbaru" in song lyrics which act as a product of modern Japanese culture. The word "ganbaru" is strongly associated with Japanese society. It reflects the industrious and energetic character of the people. The power of the word "ganbaru" was evident after Japan's defeat in World War II, when the Japanese people worked together to quickly rebuild their country from scratch. The problem addressed in this paper is how the concept of "ganbaru," which has essential meaning in Japanese society, is reflected in song lyrics as a product of modern culture. The song in question is "Guts!" by Arashi, a popular Japanese group band. Data analysis was conducted using semantic theory with qualitative descriptive methods. The analysis revealed that of the eight stanzas of the song's lyrics, the first, third, and eighth stanzas appear to contain the concept of "ganbaru," which refers to the drive or motivation to achieve a goal. The second, sixth, and seventh stanzas contain the concept of "ganbaru," which refers to not giving up and continuing to strive to achieve the ultimate goal. Furthermore, the concept of "ganbaru," which reflects persistence and sincerity, is found in the fourth and fifth stanzas.